2009
DOI: 10.1097/mao.0b013e31818a08e8
|View full text |Cite
|
Sign up to set email alerts
|

Variational Anatomy of the Human Cochlea

Abstract: The human cochlea exhibits extensive anatomic variations. These variations will influence the location of cochlear implant arrays and affect the potential of hearing preservation surgery. Our results may explain the surgeon's difficulties sometimes to insert electrode arrays even in so-called "normal" cochleae.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
105
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 252 publications
(113 citation statements)
references
References 23 publications
8
105
0
Order By: Relevance
“…13 We elected to examine cochlea volume, as it represents the entire three-dimensional space in which CI electrodes reside. While we suspected that smaller cochlear volumes would predispose to interscalar translocation and thus higher rates of SV insertion, no relation between cochlear volume and scalar electrode location was evident.…”
Section: Discussionmentioning
confidence: 99%
“…13 We elected to examine cochlea volume, as it represents the entire three-dimensional space in which CI electrodes reside. While we suspected that smaller cochlear volumes would predispose to interscalar translocation and thus higher rates of SV insertion, no relation between cochlear volume and scalar electrode location was evident.…”
Section: Discussionmentioning
confidence: 99%
“…However, it should be noted that there is likely to be great deal of variation in the insertion angles of the arrays used in this study as there is a great deal of variation in cochlear anatomy (e.g. Erixon et al, 2009). The users evaluated in Schatzer et al (2014) were implanted by the same surgeon at the same hospital as the subjects in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that conventional length electrodes often acquire a lateral wall orientation in the distal basal turn of the cochlea and beyond (1). When moving from the basal cochlea to the apex, the turning radius of the cochlea shortens, and the cross-sectional area of the scala tympani lessens (23); the combination of these 2 factors results in increased outer wall impingement and may cause fracturing of the interscalar partition and excursion of the electrode into the scala media or scala vestibuli far from the intended site of stimulation (4,9,22). Studies using computed tomography of implanted patients have shown that those with electrode positions within the scala vestibuli have diminished speech performance scores (11,21,24).…”
Section: Discussionmentioning
confidence: 99%